Malaysia’s halal ecosystem: a strategic model for global halal Economic governance - Mahamad Maifiah, Mohd Hafidz; Azam, Siddique (Islamic Business School, Universiti Utara Malaysia, 2025)
The development of the halal industry in Malaysia has been instrumental in positioning the country as one of the world's fastest-growing economies. Renowned as a global leader in the halal sector, Malaysia has significantly contributed to the halal economy that extends across diverse products and services, mainly in food and beverages, cosmetics, and pharmaceuticals. The success of the halal industry is predominantly driven by its comprehensive halal ecosystem, built on the collaborative and synergistic involvement of government agencies, industries, and consumers. The successful establishment of the halal ecosystem in Malaysia is significantly driven by key factors, including a robust halal regulatory framework comprising a systematic halal certification system and comprehensive halal guidelines and policies, as well as active halal research and development. This narrative review article delves into the Malaysia halal ecosystem, providing the structural, regulatory, and market forces that shape Malaysia’s global halal economy. Overall, this article highlights Malaysia’s economic significance and its role to serve as a blueprint for other countries to develop their halal industries.